Analisis Jarak Tempuh Perjalanan Penduduk Pada Kompleks Perumahan Citra Sudiang Indah Makassar - Stevanus Theodorus Londah; Rais Rachman; Herman Welem Tanje (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
The phenomenon of the population density level began to appear in housing. The distance from the residential location to several community activity centers is deemed necessary to conduct research. This research was conducted at Citra Sudiang Indah housing complex, which is located on the outskirts of Makassar. Data collection was carried out using questionnaires and interviews (in-depth interviews) as the research sample. This data collection was carried out to determine the characteristics of residents or households and the distance traveled by residents in the Citra Sudian Indah housing estate. The method used is multiple linear regression analysis. The results of the analysis that have been carried out show that the average respondent's journey in carrying out daily activities is the highest, which is between 5 to 10 kilometers, being the most choice for work and school/college and based on the results of the analysis, it can be seen that the distance traveled is strongly influenced by the distance traveled. , average travel time and average family income.